ACE INHIBITORS ARE RATIONAL PHARMACOTHERAPY OF ENDOTHELIAL DYSFUNCTION - M. P. Metrova; A. B. Salmina; A. I. Inzhutova; O. S. Bahmeteva (Рациональная фармакотерапия в кардиологии)
Aim. To study effects of ACE inhibitor perindopril on markers of endothelial dysfunction in therapy of patients with arterial hypertension (HT).Material and methods. 82 patients with HT, complicated by ischemic stroke were involved in the study. 30 patients with uncomplicated HT were included into control group. Antihypertensive therapy with perindopril (52 patients) or amlodipine (30 patients) was conducted additionally to standard neurotropic therapy in hypertensive patients with ischemic stroke. Phase-contrast microscopy and enzyme immunoassay were used for screening of endothelial dysfunction markers (blebbing, desquamated endothelial cells, membrane-liberated parts, sPECAM-1).Results. Reduction in levels of markers of endothelial dysfunction was observed among patients treated with perindopril in comparison with patients who did not receive ACE inhibitor or patients of control group. Target levels of blood pressure were reached in 96% of patients treated with perindopril. Сonclusion. ACE inhibitors in therapy patients with HT reduce endothelial dysfunction additionally to antihypertensive effect.